Observation of Unusual Molecular Diffusion Behaviour below the Lower Critical Solution Temperature of Water/2‐Butoxyethanol Mixtures by using Fluorescence Correlation Spectroscopy. Issue 17 (11th September 2014) - Toyouchi, Shuichi; Kajimoto, Shinji; Barzan, Daniel; Kiel, Alexander; Enderlein, Jörg; Fukumura, Hiroshi; Herten, Dirk‐Peter
Abstract The effect of solute affinity on solute diffusion in binary liquids well below the lower critical solution temperature (LCST) was studied by using fluorescence correlation spectroscopy. We measured the hydrodynamic radii of a hydrophobic and an amphiphilic fluorescent dye under systematic variation of the relative molar fractions of water/2‐butoxyethanol and, for comparison, of water/methanol mixtures, which do not show phase separation. We found that the apparent hydrodynamic radius of the hydrophobic dye almost doubled in water/2‐butoxyethanol, whereas it remained largely unchanged for the amphiphilic dye and in water/methanol mixtures. Our results indicate that the translational diffusion of solutes is influenced by transient local solution structures, even at temperatures well below the LCST. We conclude that, even far below LCST, different solutes can experience different environments in binary liquid mixtures depending on both the solute and solvent properties, all of which impact their reactivity.